7.7k views
2 votes
If cot theta = -2, find the value of cot theta + cot (theta -pi) + cot (theta-2pi)

User Argyle
by
6.0k points

1 Answer

7 votes

Given:


\cot \theta = -2

To find:

The value of
\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi).

Solution:

We know that,


\cot (\theta -n\pi)=\cot \theta ...(i)

Where n is an integer.

We have,


\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi)

Using (i), it can be written as


\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi)=\cot \theta +\cot \theta +\cot \theta


\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi)=3\cot \theta

It is given that
\cot \theta = -2.


\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi)=3(-2)


\cot \theta +\cot (\theta -\pi)+\cot(\theta -2\pi)=-6

Therefore, the value of the given function expression is
-6.

User Leslieann
by
5.6k points